Leaf nitrogen and phosphorus concentrations of woody plants differ in responses to climate, soil and plant growth form. Issue 2 (22nd June 2011) - Chen, Yahan; Han, Wenxuan; Tang, Luying; Tang, Zhiyao; Fang, Jingyun
<x xml:space="preserve">Abstract</x> Leaf chemistry is important in predicting the functioning and dynamics of ecosystems. As two key traits, leaf nitrogen (N) and phosphorus (P) concentrations set the limits for plant growth, and leaf N:P ratios indicate the shift between N‐ and P‐limitation. To understand the responses of leaf chemistry to their potential drivers, we measured leaf N and P concentrations of 386 woody species at 14 forest sites across eastern China, and explored the effects of climate, soil, and plant growth form on leaf N, P and N:P ratios. In general, leaf N and P were both negatively related to mean annual temperature and precipitation, and positively related to soil N and P concentrations. Leaf N:P ratios showed opposite trends. General linear models showed that variation in leaf N was mainly determined by a shift in plant growth form (from evergreen broadleaved to deciduous broadleaved to conifer species) along the latitudinal gradient, while variations in leaf P and N:P were driven by climate, plant growth form, and their interaction. These differences may reflect differences in nutrient cycling and physiological regulations of P and N. Our results should help understand the ecological patterns of leaf chemical traits and modeling ecosystem nutrient cycling.